2022
DOI: 10.1039/d2cc04722e
|View full text |Cite
|
Sign up to set email alerts
|

BODIPY-based metal–organic frameworks as efficient electrochemiluminescence emitters for telomerase detection

Abstract: A boron dipyrromethene (BODIPY)-based metal-organic framework (MOF) nanoemitter was for the first time designed with enhanced electrochemiluminescence (ECL) intensity due to the suppression of non-radiative dissipation originated from the ordered...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Typically, tetrakis­(4-carboxyphenyl) porphyrin with strong optical absorption and emission and distinctive electrochemical properties can be integrated into the framework to form porphyrin-based Zr-MOFs, which can overcome the aggregation-caused quenching effect and thus show great potential in ECL biosensing . Considering the high fluorescence intensity and narrow absorption/emission peaks, the integration of boron dipyrromethene (BDP) into frameworks can separate the aggregated BDP molecules, and thus 24-fold enhancement of ECL intensity is obtained due to the suppressed nonradiative energy dissipation . Furthermore, using hydroquinone and phenanthroline as redox couples, an electroactive MOF (E-MOF) with a one-dimensional zigzag chain is designed as an efficient crystalline ECL emitter in an aqueous medium (Figure A).…”
Section: Structural Design Of Reticular Ecl Nanoemittersmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, tetrakis­(4-carboxyphenyl) porphyrin with strong optical absorption and emission and distinctive electrochemical properties can be integrated into the framework to form porphyrin-based Zr-MOFs, which can overcome the aggregation-caused quenching effect and thus show great potential in ECL biosensing . Considering the high fluorescence intensity and narrow absorption/emission peaks, the integration of boron dipyrromethene (BDP) into frameworks can separate the aggregated BDP molecules, and thus 24-fold enhancement of ECL intensity is obtained due to the suppressed nonradiative energy dissipation . Furthermore, using hydroquinone and phenanthroline as redox couples, an electroactive MOF (E-MOF) with a one-dimensional zigzag chain is designed as an efficient crystalline ECL emitter in an aqueous medium (Figure A).…”
Section: Structural Design Of Reticular Ecl Nanoemittersmentioning
confidence: 99%
“…17 Considering the high fluorescence intensity and narrow absorption/emission peaks, the integration of boron dipyrromethene (BDP) into frameworks can separate the aggregated BDP molecules, and thus 24-fold enhancement of ECL intensity is obtained due to the suppressed nonradiative energy dissipation. 18 Furthermore, using hydroquinone and phenanthroline as redox couples, an electroactive MOF (E-MOF) with a one-dimensional zigzag chain is designed as an efficient crystalline ECL emitter in an aqueous medium (Figure 2A). The mixed-ligand E-MOF shows consistency in experimental and simulated powder X-ray diffraction (PXRD) (Figure 2B), suggesting its flawless crystal structure.…”
Section: Design With Electroactive Luminophore Ligandsmentioning
confidence: 99%
“…Furthermore, it was found that the individual TP-TBDA and TCNQ cannot respond to UO 2 2+ under the same conditions, manifesting that the assembly of the host−guest system is necessary for monitoring UO 2 2+ (Figure S17). Simultaneously, the presence of UO 2 2+ caused the position of the reduction peak in the CV curve of TP-TBDA@TCNQ to shift toward a more negative voltage, accompanied by the decrease of the peak current (Figure 5b), indicating that the electrode surface charge transfer of the ECL system is hindered, 47 which increases the difficulty of the electrode reaction and affects the emission of ECL.…”
Section: +mentioning
confidence: 99%
“…[29,31,32] Recently, the BODIPY molecules as building blocks are used to construct the MOFs and their photo-response property has been demonstrated. [33,34] We envisioned that the introduction of BODIPY into COFs can boost the visible-light absorption ability, endowing the BODIPY-based COFs as photocatalyst for organic transformation under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These photophysical and chemical properties of BODIPY attracted tremendous attentions and they can be widely used in photocatalysis, bioimaging, sensing and luminescent devices [29,31,32] . Recently, the BODIPY molecules as building blocks are used to construct the MOFs and their photo‐response property has been demonstrated [33,34] . We envisioned that the introduction of BODIPY into COFs can boost the visible‐light absorption ability, endowing the BODIPY‐based COFs as photocatalyst for organic transformation under mild conditions.…”
Section: Introductionmentioning
confidence: 99%